An annotated bibliography on geographic information systems applications in developing countries - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1986)
Geographic Information Systems (GIS) are needed to assist national development because GIS can manipulate and analyze geographically-referenced data to support the decision making process of an organization. A problem faced in developing countries is that decision making is not always based on integrated information. This annotated bibliography is compiled for three reasons: 1. The lack of GIS research in developing countries. 2. Although GIS are potentially useful, because of the limited amount of publish ed research, there is little information available about GIS applications. This bibliography presents relevant publications to remedy this deficiency. 3. It is believed that geographic information systems in developing countries need to be improved to facilitate the use of the integrated, comprehensive in formation to assist the country's development. This bibliography summarizes GIS procedures in general and GIS on selected countries: Costa Rica, Argentina, India, Bangladesh, Sri Lanka, and Indonesia.